Brachytherapy in Breast Cancer Treatment: Physical and Biological Aspects - Maj-Dziedzic, Monika; Brzozowska, Anna; Sikora, Marcelina; Zarzycka, Marta; Plewniok, Ines; Dubiel, Jeremiasz; Maj, Adrian; Śmietana, Greta; Warno, Martyna; Kozik, Wiktor (Journal of Education, Health and Sport, 2024)
This scientific paper focuses on the treatment of breast cancer, one of the most common cancers among women. Despite increased awareness and the popularity of screening tests, statistics indicate a significant rise in incidence. The paper presents breast-conserving treatment methods, including brachytherapy, as a modern technique with promising outcomes. It describes the physical properties of ionizing radiation used in brachytherapy, discussing the photoelectric effect, Compton effect, and the phenomenon of pair production. The paper then delves into the biological effects of ionizing radiation, emphasizing the dependence on the cell cycle phase. It highlights lethal, sublethal, and potentially lethal cellular damage, categorizing the effects of radiation interaction into early and late responses. The discussion transitions to the application of brachytherapy in breast cancer treatment, focusing on various techniques such as LDR, PDR, and HDR. The paper provides a detailed description of brachytherapy’s use in breast-conserving treatment, considering contraindications, treatment planning, and Accelerated Partial Breast Irradiation (APBI) techniques. The radioisotopes used in brachytherapy are also presented, with special attention to Iridium-192. The physical and practical aspects related to this isotope are discussed, along with other commonly used radioisotopes such as Cesium-137, Cobalt-60, and Strontium-90. The paper concludes with a summary, emphasizing the significance of brachytherapy in breast cancer treatment and outlining its prospects for development. The authors highlight precision and shortened therapy duration.